Improved targeting of the 16S rDNA nanopore sequencing method enables rapid pathogen identification in bacterial pneumonia in children - Chen, Yinghu; Mao, Lingfeng; Lai, Dengming; Xu, Weize; Zhang, Yuebai; Wu, Sihao; Yang, Di; Zhao, Shaobo; Liu, Zhicong; Xiao, Yi; Tang, Yi; Meng, Xiaofang; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives To develop a rapid and low-cost method for 16S rDNA nanopore sequencing. Methods This was a prospective study on a 16S rDNA nanopore sequencing method. We developed this nanopore barcoding 16S sequencing method by adding barcodes to the 16S primer to reduce the reagent cost and simplify the experimental procedure. Twenty-one common pulmonary bacteria (7 reference strains, 14 clinical isolates) and 94 samples of bronchoalveolar lavage fluid from children with severe pneumonia were tested. Results indicating low-abundance pathogenic bacteria were verified with the polymerase chain reaction (PCR). Further, the results were compared with those of culture or PCR. Results The turnaround time was shortened to 6~8 hours and the reagent cost of DNA preparation was reduced by employing a single reaction adding barcodes to the 16S primer in advance. The accuracy rate for the 21 common pulmonary pathogens with an abundance ≥ 99% was 100%. Applying the culture or PCR results as the gold standard, 71 (75.5%) of the 94 patients were positive, including 25 positive cultures (26.6%) and 52 positive quantitative PCRs (55.3%). The median abundance in the positive culture and qPCR samples were 29.9% and 6.7%, respectively. With an abundance threshold increase of 1%, 5%, 10%, 15% and 20%, the test sensitivity decreased gradually to 98.6%, 84.9%, 72.6%, 67.1% and 64.4%, respectively, and the test specificity increased gradually to 33.3%, 71.4%, 81.0%, 90.5% and 100.0%, respectively. Conclusions The nanopore barcoding 16S sequencing method can rapidly identify the pathogens causing bacterial pneumonia in children.